Use of the alvarado score for assessment of abdominal pain in a women`s soccer player - Gray, C. (International Journal of Athletic Therapy & Training, 2022)
The Alvarado score is used in emergency rooms to determine probability of appendicitis and provide a recommendation for care. A women`s soccer player presented to the athletic training clinic with right lower quadrant pain. She was evaluated and due to a differential diagnosis of appendicitis, the Alvarado score was used for screening. Based on her score, she was referred to the emergency room and, after diagnostic testing, was found to have a ruptured ovarian cyst. The Alvarado score was helpful in determining the need for referral when used in the clinical setting.